1953
DOI: 10.1021/ja01109a005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Disproportionation Rates at the Dropping Mercury Electrode

Abstract: Vol. 75 to the electrode at a different rate than the symmetrical trans form. It follows that the migration current, and hence the limiting current, would be different for the cis ion than for the trans,2SThe situation in the absence of supporting electrolyte is complicated by the formation of electrolyte (nitrite ions, for example) during the reduction, as well as by stirring effects associated with maxima which may not completely disappear even at more negative potentials. Absolute values for limiting curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1960
1960
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…In a systematic study using a gold electrode, the effect of acidity on the magnitude of redox waves of U(VI)/U(V) was reported. It was found that in strongly acidic solutions (i.e., pH 62) the decomposition of U(V) was enhanced and therefore the anodic wave of U(V) to U(VI) decreased [27,[31][32][33][34]. Kuta and Yeager studied the redox mechanism of uranyl on a gold electrode in perchlorate solution, and thoroughly reported on similar findings [35,36].…”
Section: Electrochemistry Of Uranylmentioning
confidence: 79%
See 2 more Smart Citations
“…In a systematic study using a gold electrode, the effect of acidity on the magnitude of redox waves of U(VI)/U(V) was reported. It was found that in strongly acidic solutions (i.e., pH 62) the decomposition of U(V) was enhanced and therefore the anodic wave of U(V) to U(VI) decreased [27,[31][32][33][34]. Kuta and Yeager studied the redox mechanism of uranyl on a gold electrode in perchlorate solution, and thoroughly reported on similar findings [35,36].…”
Section: Electrochemistry Of Uranylmentioning
confidence: 79%
“…While these findings are not simple to interpret, it is likely to assume that a portion of the uranium(IV) product from the disproportionation of UO þ 2 reaches the electrode and is oxidized. This assumption is based on several past publications [31][32][33][34] …”
Section: Electrochemistry Of Uranylmentioning
confidence: 99%
See 1 more Smart Citation
“…In less acidic solutions the situation is simplified because the disproportionation of U(V) does not take place (13), but studies in weakly acid to neutral aqueous media (13,14) are few.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of U(V1) has been extensively studied in aqueous media by different electrochemical methods (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).2 Most of these studies have been carried out in acidic (HCIO,, HCl, H2S04, HN03) media (2-1 1). In sufficiently acidic solution, the reduction mechanism (12) is that uranyl is reduced in a one-electron step and that the resulting U(V) species disproportionates, regenerating U(W).…”
Section: Introductionmentioning
confidence: 99%